2021
DOI: 10.1021/acs.jced.1c00144
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Equilibrium and Binodal Curves for Aqueous Solutions of NH3, NH4HCO3, MDEA, and K2CO3

Abstract: Solid−liquid equilibrium (SLE) data were obtained at 0.1 MPa for binary, ternary, and quaternary aqueous solutions containing ammonia (NH 3 ), ammonium bicarbonate (NH 4 HCO 3 ), methyl diethanolamine (MDEA), and potassium carbonate (K 2 CO 3 ) using a modified Beckmann apparatus. The reproducibility of the experimental method was verified by measuring the SLE of aqueous solutions containing NH 3 , K 2 CO 3 , or MDEA in a temperature range between 237 and 273 K. A total of 120 new data points were measured for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In addition to the listed species, potassium and mixed potassium–ammonium salts may precipitate in the solution . Solid formation in aqueous MDEA solutions has been the topic of investigation in an earlier study . Additionally, several authors have indicated the precipitation of ammonium carbamate (NH 2 COONH 4 ) due to a gas-phase reaction between CO 2 and ammonia. The information regarding SLE in these systems was used to ensure that no solids were present in the system during the VLE experiments.…”
Section: Theory and Calculationmentioning
confidence: 99%
“…In addition to the listed species, potassium and mixed potassium–ammonium salts may precipitate in the solution . Solid formation in aqueous MDEA solutions has been the topic of investigation in an earlier study . Additionally, several authors have indicated the precipitation of ammonium carbamate (NH 2 COONH 4 ) due to a gas-phase reaction between CO 2 and ammonia. The information regarding SLE in these systems was used to ensure that no solids were present in the system during the VLE experiments.…”
Section: Theory and Calculationmentioning
confidence: 99%